DIAGNOSIS OF NEPHROTIC SYNDROME IN CHILDREN WITH THE MOBILE WEB-BASED DEMSTER SHAFER METHOD - Dandi Fratama Wardana; Samsudin Samsudin (ZERO: Jurnal Sains, Matematika dan Terapan, 2023)
Children's health is certainly a concern for parents, especially coupled with various types of viruses that became outbreaks in 2020. Therefore, parents' concerns about their children become greater. Without proper treatment and handling, usually Nephrotic Syndrome disease will assume everything that is done is right even though it deviates. In the field of medicine, the precision with which an illness is diagnosed and the speed with which the diagnosis is made are both crucial. The patient's health will suffer as a result of treatment decisions being delayed due to misdiagnosis. However, there are occasionally only a few doctors available. The Dempster Shafer technique produces precise, quick, and accurate diagnoses by garnering the respect of experts based on their expertise. In this study, disease will be identified using the Dempster-Shafer approach. This study's output is an expert system that, without consulting an expert directly, can determine whether a person has a condition based on the symptoms they are experiencing.  By contrasting the outcomes of expert diagnostics with those generated by the system, high accuracy, testing of this system comprises determining the validity of the system's accuracy value.